The Effects of Lighting and Interpersonal Distance on Counseling Interactions - Dumont, Florent; Lecomte, Conrad (Canadian Journal of Counselling and Psychotherapy, 2012)
This study investigated the effect of intensity of lighting andinterpersonal distance in an analog counseling situation on an array ofcounseling variables: e.g., communication of empathy, duration of silence,duration of speech, number of interactions. Excerpts from initial sessionswere randomly selected, rated, and analyzed. Results showed a significantinteractive effect of lighting and distance on the communication of empathy.Both significant and non-significant results were discussed.